2017
DOI: 10.1038/s41522-017-0026-1
|View full text |Cite|
|
Sign up to set email alerts
|

Norgestimate inhibits staphylococcal biofilm formation and resensitizes methicillin-resistant Staphylococcus aureus to β-lactam antibiotics

Abstract: Formation of bacterial biofilms on medical devices can cause severe or fatal infectious diseases. In particular, biofilm-associated infections caused by methicillin-resistant Staphylococcus aureus are difficult to eradicate because the biofilm is strongly resistant to antibiotics and the host immune response. There is no effective treatment for biofilm-associated infectionss, except for surgical removal of contaminated medical devices followed by antibiotic therapy. Here we show that norgestimate, an acetylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 45 publications
(48 reference statements)
0
28
0
Order By: Relevance
“… Yoshii et al (2017) have shown that norgestimate, a compound primarily used for oral contraception and hormone replacement therapy ( Henzl, 2001 ) but also investigated as a potential antibiofilm/antibiotic agent, was able to inhibit biofilm formation by staphylococcal strains. It did so via inhibiting production of a polysaccharide adhesin and proteins in the extracellular matrix, thus affecting biofilm structure and integrity ( Yoshii et al, 2017 ).…”
Section: Biofilms In Infectionsmentioning
confidence: 99%
“… Yoshii et al (2017) have shown that norgestimate, a compound primarily used for oral contraception and hormone replacement therapy ( Henzl, 2001 ) but also investigated as a potential antibiofilm/antibiotic agent, was able to inhibit biofilm formation by staphylococcal strains. It did so via inhibiting production of a polysaccharide adhesin and proteins in the extracellular matrix, thus affecting biofilm structure and integrity ( Yoshii et al, 2017 ).…”
Section: Biofilms In Infectionsmentioning
confidence: 99%
“…MRSA biofilm-associated infections are difficult to be eradicated because the biofilm is strongly resistant to wide variety of antibiotics and the host immune response. 3 The vast majority of food-borne outbreaks caused by antimicrobial-resistant pathogens are the result of the consumption of contaminated foods of either animal-origin or multi-ingredient foods. 42 In the present study, MAR index among food strains, MRSA from meat showed the highest value as 0.61±0.1 (Figure 1), while among food worker strains, fingernail strains showed 0.57±0.14.…”
Section: Resultsmentioning
confidence: 99%
“…1 MRSA resists β-lactams antibiotics (penicillins, cephalosporins, monobactams, and carbapenems groups) 2 which are primarily conferred by the acquisition of mecA gene encoding penicillin binding protein (PBP 2a). 3 This protein is an important factor in biofilm accumulation, 4 then MRSA adhere to biotic or abiotic surfaces 5 and be protected against hostile environments. 6 MRSA antimicrobial resistance might be increased on harbouring any of biofilm producing gene (ica operon).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of biofilm composition formed in IMDM and TSB revealed that, indeed, after 4 h of growth, very minimal amounts of eDNA were seen in any of the biofilms. However, biofilms formed in IMDM did contain N-acetylglucosamine-containing components, presumably PIA, which was visualized by wheat germ agglutinin (WGA) lectin staining (39). After 24 h of growth, dead cells and eDNA were observed in biofilms grown in TSB but not biofilms grown in IMDM.…”
Section: Discussionmentioning
confidence: 99%